PEMENUHAN KEBUTUHAN ANAK SAAT PANDEMI COVID-19 DI PANTI SOSIAL ASUHAN ANAK AL-MUBAROKAH LEBAK BULUS JAKARTA - Anggiani, Anggiani; Yuliani, Dwi; Susilawati, Susilawati (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2021)
Every human being needs the fulfillment of basic needs in life, as well as children. During the covid-19 pandemic the fulfillment of the needs of orphanage children needs to be considered. This study aims to find out an in-depth and empirical picture of the fulfillment of children's needs during the covid-19 pandemic at al-Mubarokah Children's Orphanage which includes aspects of physiological needs, security needs and social needs. The research uses qualitative approach with descriptive method. Informants in this study were three caregivers, two caretakers and three foster children. Data collection is conducted with in-depth interviews, observations and documentation studies. The results showed that social needs seen from sub-aspects of social interaction showed good results. While aspects of physiological needs and the need for security have not been maximized. In an effort to improve physiological needs and security needs, a program was designed. The program proposed by researchers is Panti Sigap for Children's Needs during the Covid-19 Pandemic. The purpose of this program is to improve the fulfillment of children's needs related to aspects of physiological needs and security. This program uses the groupwork method.